IMPLEMENTASI PENDIDIKAN KARAKTER DI SD NEGERI 33 SAWAHAN - Hasmai Bungsu Ladiva; Bima Prakarsa Arzfi; Rafhi Febryan Putera (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Character education is important to be instilled in students from an early age, considering the great influence of student character on their future lives. This study examines the implementation of character education in one of the elementary schools in Padang City, namely SD Negeri 33 Sawahan. Using a qualitative phenomenological research type, this study attempts to explain the implementation strategy, experience, handling, and various activities related to character education in SD Negeri 33 Sawahan, Padang City. The results obtained are that SD Negeri 33 Sawahan, Padang City has implemented character education both inside and outside the classroom. Positive and negative reinforcement are used in a balanced manner to ensure student consistency in implementing character values. However, technological advances and various recent discoveries will produce various different challenges, so the implementation of character education must develop in line with the times.